Squaring both sides of the equation results in the equation,(x+1=x+6-1). Option A is correct.
A mathematical statement consisting of an equal symbol between two algebraic expressions with the same value is known as an equation.
The given equation is;
[tex]\rm \sqrt{x+1} = \rm \sqrt{x+6} = 1[/tex]
After squaring we get;
[tex]\rm (\sqrt{x+1})^2 = \rm ( \sqrt{x+6})^2 = 1^2 \\\\ x+1 = x+6=1 \\\\\ x+1=1+6-1[/tex]
The equation (x+1=x+6-1) is created by squaring both sides of the equation.
Hence option A is correct.
To learn more, about equations, refer;
https://brainly.com/question/10413253
#SPJ1